2022
DOI: 10.3389/fmed.2022.915548
|View full text |Cite
|
Sign up to set email alerts
|

The photosensitizer-based therapies enhance the repairing of skin wounds

Abstract: Wound repair remains a clinical challenge and bacterial infection is a common complication that may significantly delay healing. Therefore, proper and effective wound management is essential. The photosensitizer-based therapies mainly stimulate the photosensitizer to generate reactive oxygen species through appropriate excitation source irradiation, thereby killing pathogenic microorganisms. Moreover, they initiate local immune responses by inducing the recruitment of immune cells as well as the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 124 publications
(165 reference statements)
0
7
0
Order By: Relevance
“…Therefore, the identification of an effective mastitis treatment that does not promote the selection of drug-resistant populations is extremely necessary. Photodynamic therapy has demonstrated remarkable efficacy in the treatment of microbial diseases in humans [ 15 , 16 ]. However, limited research has explored its application in bovine mastitis pathogens and drug-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of an effective mastitis treatment that does not promote the selection of drug-resistant populations is extremely necessary. Photodynamic therapy has demonstrated remarkable efficacy in the treatment of microbial diseases in humans [ 15 , 16 ]. However, limited research has explored its application in bovine mastitis pathogens and drug-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also explored applications in treating infected wounds, especially those associated with MDR bacteria. The results suggest that antibacterial PDT can be beneficial in promoting wound healing and controlling bacterial growth [144,145]. In the field of periodontal diseases, clinical trials have shown promising results for treating chronic periodontitis, a common bacterial infection that affects the gums and supporting structures of the teeth [146][147][148][149].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Visible light can also be applied in the form of photodynamic therapy (PDT) [ 33 ]. PDT employs a combination of non-toxic dyes (called photosensitizers) combined with visible light for the subsequent formation of reactive oxygen species (ROS), intending to eliminate microorganisms, cancer cells, and unwanted tissues [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, erosions, infection, and sterile pustules are possible adverse effects, although they are rare. In the long term, pigment changes and scarring can occur [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation